What OBE did to us!' : the experiences of four Cape Town secondary school teachers - Christian, DesirÃ© (School of Education, 2014)
This dissertation is a study of the impact of OBE (Outcomes-based Education) and C2005 (Curriculum 2005) on the professional lives and teaching of a select group of high school teachers. The research was a combination of a case study approach and reflective professional practice. It sought to identify and explain key aspects that had produced such a marked alteration in the position of the teachers within such a short period.